The Relevance of Weton Calculation Tradition in Javanese Culture in Determining Marriage Contracts: A Sharia Perspective - Ardhalia Nirmala Putri; Fathimah Husnayain; Fatimah Fauziah; Khasna Nurjannah; Nadya Qurrota A’yun; Naurotul Himmah Al-Atsariyah; Nur Rohana; Rika Roichatul Janah; Febryan Hidayat; Bahar Khoeruzaad (Walidem Institute and Publishing (WIP), 2024)
The purpose of this study is to reveal the calculation of weton, which is usually used as a reference in determining the date of marriage, whether or not a relationship is good, and determining a good soul mate, in the view of sharia. This research uses qualitative methods with a descriptive approach. Data was collected through literature studies to identify and analyze relevant information related to the use of weton in Javanese society and how perceptive it is in Islamic law. The results of the study concluded that marriage is the beginning of a new life that affects offspring and society. However, success in marriage does not only depend on weton alone, but communication between the two and mutual understanding and commitment to mutual trust also have an important role in the success of marriage. In Javanese wedding customs, weton calculations are usually used to determine execution decisions. However, this hadith is forbidden in Islam because it contradicts the Shari'a and can give rise to shirk, where no one can know ghoib other than Allah including sustenance, soul mate, and calamity. This research is expected to be able to add insight and make people understand the main basis of marriage, namely Islamic principles, not only about customs and cultural traditions.